1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Finding Max/Min Values on Parametric Functions

  1. Nov 12, 2011 #1
    1. The problem statement, all variables and given/known data
    Consider the function F(x,y) = 1 - x3 - y2 + x3y2. Consider the curve C given parametrically as x(t) = t1/3, y(t) = t1/2 for t ≥ 0. Determine the minimum and maximum of F(x,y) along the curve C.

    3. The attempt at a solution
    I think this is basically a max/min problem with a constraint function, so I will try to use Lagrange multipliers.

    Fx = -3x2 + 3x2y2
    Fy = -2y + x3*2y

    Fx(t1/3,t1/2) = -3t2/3 + 3t5/3 = 1/(3t2/3) * λ
    Fy(t1/3,t1/2) = -2t1/2 + 2t3/2 = 1/(2t1/2) * λ

    9t4/9 * (-1 + t) = λ
    4t1/4 * (-1 + t) = λ

    9t4/9 = 4t1/4

    t7/36 = 4/9
    t = (4/9)36/7

    And at this point I'm thinking there's no way this problem is this disgusting. Ideas on where I went wrong?
  2. jcsd
  3. Nov 12, 2011 #2


    Staff: Mentor

    I don't get how you arrived at the last expression. The expression just before it can be factored to 3t2/3(-1 + t)
    I'm not getting what you're doing here, either.
  4. Nov 12, 2011 #3
    I arrived at the last expression by setting

    Fx(t1/3,t1/2) = -3t2/3 + 3t5/3

    equal to the derivative of x(t), which I found to be 1/(3t2/3), and then multiplied by the constant λ, as required by the Lagrange multiplier method. Similarly, I let Fy(t1/3,t1/2) equal y'(t) multiplied by λ. By factoring, as you suggested, I can solve easily for λ, which is what you see above in,

    9t4/9 * (-1 + t) = λ
    4t1/4 * (-1 + t) = λ

    However, I don't think this method is the proper way to go about answering the problem, since it gives a rather peculiar answer, namely t = (4/9)36/7
  5. Nov 13, 2011 #4


    User Avatar
    Science Advisor

    Personally, I wouldn't use Lagrange multipliers- it seems to me much easier just to substitute the values of x and y in terms of t. With [itex]x= t^{1/3}[/itex] and [itex]y= t^{1/2}[/itex], [itex]F(x,y)= 1- x^3- y^2+ x^3y^2=1- t- t+ t^2= t^2- 2t+ 1= (t-1)^2[/itex]. Now, you don't even need to differentiate!
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook